Nine cycle of mass section to increased oil content in the two synthetics populations of maize (Zea mays L.) - Rošulj Milorad; Vančetović Jelena; Todorović Goran (Selekcija i Semenarstvo, 2001)
The objectives of this study were to estimate changes in oil content and grain yield in the maize populations DS7u and YuSSSu. As estimations were performed at CO and C9 for both populations, it was possible to observe changes occurring following long-term mass selection for high oil content. The synthetic population DS7u was developed by recombination of 29 inbreeds of Yugoslav, Canadian and US origin. The synthetic population YuSSSu is an Iowa Stiff Stalk Synthetic - BSS(R)C5. The following statistical and genetic parameters were analyzed: means, frequency distribution, components of genetic variance and heritability. Progenies were derived according to the North Carolina Design II. Results were indicated that nine cycles of selection led to statistically significant increase in oil content and statistically significant decrease for grain yield in both populations. Estimates of additive and dominance variances for grain oil content were highly significant in CO and C9 of the population DS7u. Dominance variance showed significance in the initial cycle of the population YuSSSu, but it disappeared in the course of nine cycles of mass selection. Additive and dominance variances for grain yield were highly significant in both initial populations. Loss of significance did not result from selection, while the proportion of dominance vs. additive variance became greater. High narrow-sense heritability was detected for grain yield and oil content in the initial cycles of both populations. Mass selection resulted in increased heritability for oil content in the DS7u population. .